The Effects of Different Intensity of Thinning on the Development in Scots Pine (Pinus sylvestris L.) Stands in Kazakh Uplands - EBEL, Andrei V.; EBEL, Yekaterina İ.; ZALESOV, Sergei V.; AYAN, Sezgin (Alinteri Zirai Bilimler Dergisi, 2019)
The search for more accurate methods of predicting the growth and development of forest stands became the most urgent task set for foresters of Kazakhstan to determine the permissible interventions in the natural course of the life of plantings, provide high durability and resilience in forests. The aim of the study was to identify the effects of diameter and density of Scots pine stands of Kazakh Uplands on their growth and productivity and the related productivity of single plantation stands taking into account the conditions of growth and development of internal factors as well as further study of the methodology for assessing the forestry cost-effectiveness and improvement thinning. To achieve this aim, effects of varied felling intensities on Scots pine stands were studied. The most common two forest types in upland Scots pine forests were chosen as permanent sample plots; the dead pine-lichen and moss pine-grass. The results showed that improvement thinning of moderate and severe intensity which are more profitable should be done in Scots pine forests of Kazakh Upland as well as carrying out such thinning increases the yield of the larger logs and increases the value of the left stand.
Keywords: ECONOMIC EFFICIENCY; forestry activities; Scots pine stands; felling of forests; economic efficiency; Ziraat, Veterinerlik ve Gıda Bilimleri; FORESTRY ACTIVITIES; SCOTS PINE STANDS; FELLING OF FORESTS; Agricultural, Veterinary and Food Sciences; 15. Life on land